Lung Cancer Cell-Derived Exosomal let-7d-5p Down-Regulates OPRM1 to Promote Cancer-Induced Bone Pain - Li, Xihan; Chen, Yu; Wang, Jialun; Jiang, Chengfei; Huang, Ying (Frontiers in Cell and Developmental Biology, 2021)
Cancer-induced bone pain (CIBP) is the pain caused by metastasis of malignant tumors to the bone, accounting for more than half of all chronic cancer pain, which seriously affects the quality of life among tumor patients. Up to 40% of patients with advanced lung cancer suffer from CIBP. MicroRNA (miRNA) transfers between cells through exosomes, mediates cell-to-cell communication, and performs various biological functions. Studies have shown that miRNAs secreted by cancer can modify the tumor microenvironment, but whether exosome-mediated miRNA transfer plays a role in CIBP is still unknown. In this study, the expression levels of 15 miRNAs in exosomes derived A549 cells and 18 miRNAs in exosomes derived NCI-H1299 cells were significantly up-regulated, and qRT-PCR further confirmed that the level of let-7d-5p was increased most considerably. In vitro, exosomal let-7d-5p (EXO let-7d-5p) can be taken up by dorsal root ganglion (DRG) neurons and inhibit the protein level of the target gene opioid receptor mu 1 (OPRM1). EXO let-7d-5p was further confirmed to be involved in the generation and maintenance of CIBP in vivo. Our findings clarify the molecular mechanism of CIBP caused by the inhibition of OPRM1 by EXO let-7d-5p, providing new clues and intervention targets for the prevention and treatment of CIBP.